HUBUNGAN SIKAP MAHASISWA DENGAN PROFESI BIDAN TERHADAP PRESTASI BELAJAR MAHASISWA PRODI DIII KEBIDANAN SEMESTER II UNIVERSITAS RESPATI YOGYAKARTA - Komaria Susanti (STIKes Al-Insyirah Pekanbaru, 2020)
ABSTRACT One of health worker who involve directly toward maternal and child health service is midwife. According to Raharjo (2009), there were 230.000-250.000 midwives in Indonesia. The number of midwives more than the number of villages. It is expected the midwives are competent and professional. Objective: Identifying relationship between students attitude toward midwife profession and learning achievement of second semester students of DIII Midwifery Program at Universitas Respati Yogyakarta. This was a descriptive analytic study with cross sectional approach. Population were all of second semester students of DIII Midwifery Program. Sample was 143 students taken using proportionate to population size. Result: Spearman Rank result showed that students attitude toward midwife profession significantly associated with learning achievement statistic or p value <0,05 . There were a relationship between students attitude toward midwife profession and learning achievement of second semester students of DIII Midwifery Program at Universitas Respati Yogyakarta. Keywords: attitude, midwife profession, learning achievement